-3n+4=n-3n

Simple and best practice solution for -3n+4=n-3n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3n+4=n-3n equation:


Simplifying
-3n + 4 = n + -3n

Reorder the terms:
4 + -3n = n + -3n

Combine like terms: n + -3n = -2n
4 + -3n = -2n

Solving
4 + -3n = -2n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '2n' to each side of the equation.
4 + -3n + 2n = -2n + 2n

Combine like terms: -3n + 2n = -1n
4 + -1n = -2n + 2n

Combine like terms: -2n + 2n = 0
4 + -1n = 0

Add '-4' to each side of the equation.
4 + -4 + -1n = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -1n = 0 + -4
-1n = 0 + -4

Combine like terms: 0 + -4 = -4
-1n = -4

Divide each side by '-1'.
n = 4

Simplifying
n = 4

See similar equations:

| 8.5w=-119 | | (2x-y+5z)(2x-y-5z)= | | 9x+(x+1)=17-4x | | 4w-6=11 | | 7y+5x=148 | | (x-6)/4 | | (k-2)x^2-5x+2=0 | | 5(-3-2m)+7m= | | -35x=35 | | 20=2x+1.5y | | 14.82+w=28.82 | | log(4x+3)+log(3)=log(11x+12) | | 2x+6y=168 | | 7/9x3 | | y=-1(-6)+6 | | -141=-6+5(1+7x) | | 2(x-1)-6=10-(1-x)+6 | | 12x^2-1=-8x | | 8x=6-12 | | -15+1y=-6 | | 7x-(x-1)=31 | | 5-9k+1+k-2(7-k)=p | | 2(7-x)+2x=510 | | 3x^2-26x=9 | | 38=j-10 | | y=2/9x-3 | | 126=-2(1+8p) | | 8x^2-2x=7x^2-5x+10 | | 5x-2(2x+9)=-21 | | 26+m=110 | | 1/5(d-200)=160 | | 2x-21y-500000=0 |

Equations solver categories